Data on prevalence of additive colors in local food and beverage products, Tehran, Iran - Asadnejad, Sahar (Data Brief, 2018)
The quality check and determination of permitted and non-permitted additive colors in food products is very important for customer׳s right protection and health. This survey was undertaken to demonstrate the frequently use of additive colors and products targeted to color adulteration in Iranian foods and beverages. From the 1120 of the samples, 18.86% contained artificial colors, 11.89% contained natural colors and 69.25% of samples had no additive colors. Tartrazine (E102) was the only non-permitted artificial dye used in samples. Among products with additive colors, only 4.38% of samples failed to meet with national Iranian standard and 61.23% of non-compliance samples were from non-industrial sectors and mostly were saffron and food containing saffron such as saffron rock candy and saffron chicken. These places and products quality are main the concern to solve the color adulteration in Iranian food market.